Biotypes of HIV-associated neurocognitive disorders based on viral and immune pathogenesis. Issue 3 (June 2022) - Johnson, Tory P.; Nath, Avindra
Abstract : Purpose of review: HIV-associated neurocognitive disorders (HAND) continues to be prevalent in people living with HIV despite antiretroviral therapy. However, understanding disease mechanisms and identifying therapeutic avenues has been challenging. One of the challenges is that HAND is a heterogeneous disease and that patients identified with similar impairments phenotypically may have very different underlying disease processes. As the NeuroAIDS field is re-evaluating the approaches used to identify patients with HIV-associated neurological impairments, we propose the subtyping of patients into biotypes based on viral and immune pathogenesis. Recent findings: Here we review the evidence supporting subtyping patients with HIV-associated neurological complications into four biotypes: macrophage-mediated HIV encephalitis, CNS viral escape, T-cell-mediated HIV encephalitis, and HIV protein-associated encephalopathy. Summary: Subtyping patients into subgroups based on biotypes has emerged as a useful approach for studying heterogeneous diseases. Understanding biotypes of HIV-associated neurocognitive impairments may therefore enable better understanding of disease mechanisms, allow for the development of prognostic and diagnostic markers, and could ultimately guide therapeutic decisions.